2021 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2021
DOI: 10.1109/smc52423.2021.9658674
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking Analytics for Mental States Assessment – A Review

Abstract: With the increasing demands on mutual understanding between human beings and advanced systems, objectively measuring and monitoring human mental states in a non-intrusive way has been a hot topic in recent days. Eye-tracking data has long been found to be a kind of suitable bio signals in measuring human mental states, as visual is the first channel of information collection and eye-tracking data shows the process of human-system interactions. Traditionally, many studies have been conducted to confirm the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…Researchers have found that the mental stress is correlated with pulse rate and pupil dilation when individuals are exposed to virtual environment [30]. Mental stress has been successfully detected by researchers from different eye tracking data such as gaze-bin and entropy by using machine learning, deep learning techniques [31].…”
Section: Researchers Have Successfully Detected the Affective States ...mentioning
confidence: 99%
“…Researchers have found that the mental stress is correlated with pulse rate and pupil dilation when individuals are exposed to virtual environment [30]. Mental stress has been successfully detected by researchers from different eye tracking data such as gaze-bin and entropy by using machine learning, deep learning techniques [31].…”
Section: Researchers Have Successfully Detected the Affective States ...mentioning
confidence: 99%
“…The use of machine learning and statistical analysis applied to physiological data has shown potential in monitoring mental health and assessing human mental states [20]. Machine learning models can be trained on labeled eye-tracking data to classify the user's mental state [21], [22]. However, more investigation is required to develop the ideal eye-tracking paradigms and machine-learning algorithms for correctly diagnosing people with Autism Spectrum Disorder (ASD) and other neurological and neuropsychiatric illnesses.…”
Section: B Model Selectionmentioning
confidence: 99%